2002
DOI: 10.1073/pnas.202300099
|View full text |Cite
|
Sign up to set email alerts
|

Functional correction of adult mdx mouse muscle using gutted adenoviral vectors expressing full-length dystrophin

Abstract: Duchenne muscular dystrophy is a lethal X-linked recessive disorder caused by mutations in the dystrophin gene. Delivery of functionally effective levels of dystrophin to immunocompetent, adult mdx (dystrophin-deficient) mice has been challenging because of the size of the gene, immune responses against viral vectors, and inefficient infection of mature muscle. Here we show that high titer stocks of three different gutted adenoviral vectors carrying full-length, muscle-specific, dystrophin expression cassettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 39 publications
4
61
1
3
Order By: Relevance
“…These so-called 'gutted' adenoviruses have a high cloning capacity and are able to accommodate the full-length dystrophin cDNA. They have successfully delivered human 16 and mouse 16,17 full-length dystrophin into the mdx muscle achieving very high levels of transfection and improved muscle function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These so-called 'gutted' adenoviruses have a high cloning capacity and are able to accommodate the full-length dystrophin cDNA. They have successfully delivered human 16 and mouse 16,17 full-length dystrophin into the mdx muscle achieving very high levels of transfection and improved muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…6 There are many strategies for the induction of de novo dystrophin expression as a therapeutic approach for the treatment of DMD. These include systemic drug delivery, 7 gene modification at DNA and RNA levels, [8][9][10][11] cell transplantation [12][13][14] and gene delivery with a wide range of both viral [15][16][17] and nonviral [18][19][20] delivery systems. However, therapeutic levels, together with a stable longterm presence of dystrophin at the sarcolemma of the muscle fibres, are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these immune responses could be blunted by the use of modified vector backbones (eg by using 'gutted' vectors), muscle-specific promoters (in either Ad or rAAV vectors), or by using ultrapurified vector preparations (eg HPLC purification of lentiviral vectors). 5,6,23,24,43 However, we observed that muscles transduced with the L-CK6-ntsLacZ still showed decreased b-galactosidase activity with increasing time (data not shown), while dystrophin expression from the L-CMV-DH2-R19 vector appeared stable (Figure 2b).…”
Section: Discussionmentioning
confidence: 89%
“…37,38 Thus, Ad vectors were found to primarily target satellite cells, myoblasts and immature myofibers, and the highest transduction of skeletal muscle mediated by Ad is achieved in neonatal or regenerating muscle tissue. 5,[37][38][39] Effective transduction by VSV-G-pseudotyped lentiviral vectors also requires appropriate expression of several proteins such as heparan sulfate proteoglycans and glycosaminoglycans (GAGs) on target cell surfaces. 40 However, the seeming inefficiency of lentiviral transduction of muscle in vivo relative to cultured cell lines may not be due primarily to differences in receptor levels, since we efficiently transduced freshly isolated single myofiber fragments and primary myoblasts from mice (Figures 4a, b, and 5b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation